2009
DOI: 10.1007/s10620-009-1027-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Meal and Water Loading on Heart Rate Variability in Children with Functional Dyspepsia

Abstract: FD in children is associated with an abnormal autonomic response best demonstrated following a meal. The relationship between baseline sympathovagal balance and water load volume in FD patients is distinctly different from the relationship in control children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
14
2
Order By: Relevance
“…Friesen and colleagues [26] investigated the HRV reactivity of 9 children suffering from Rome III functional dyspepsia (FD; mean age 13 years) following a test meal or rapid water loading. They were compared to 28 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Friesen and colleagues [26] investigated the HRV reactivity of 9 children suffering from Rome III functional dyspepsia (FD; mean age 13 years) following a test meal or rapid water loading. They were compared to 28 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding children with AP, Puzanonva and colleagues [25] and Friesen and colleagues [26] found differentiating HRV reactivity patterns following cognitive challenge or meal ingestion. In adults with IBS, only one study investigated the reactivity of the HRV.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between the groups before or after the solid meal. We previously found an increased LF/HF ratio following a solid meal (but not water) in controls as opposed to patients with FD defined by Rome III criteria . In controls, SNDD increased significantly after the liquid (but not the solid) meal, but did not change after either meal in patients with FD.…”
Section: Discussionmentioning
confidence: 81%
“…There is a paucity of studies assessing autonomic responses to a meal in children and adolescents with FD. In a single study, a loss of the normal response, a postprandial shift in autonomic balance, was demonstrated in youth with FD (according to Rome III) following a solid meal; however, there was no difference between youth with FD and controls following water loading …”
Section: Introductionmentioning
confidence: 95%
“…Different studies have evaluated how the hydration state may influence the sympathovagal balance and which is the effect of dehydration on the health status of athletes. Moreover, the imbalance of the autonomic nervous system in functional dyspeptic patients, and the consequent visceral hypersensitivity, has been widely demonstrated . In our study, we evaluated for the first time how dehydration, but in particular rehydration with different types of water, may influence sympathovagal balance in dyspeptic athletes and trigger the onset GI symptoms .…”
Section: Discussionmentioning
confidence: 99%